2007
DOI: 10.1021/es0717360
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution, Sorption, and Kinetics Involved in Systems Containing Explosives, Water, and Soil

Abstract: Knowledge of explosives sorption and transformation processes is required to ensure that the proper fate and transport of such contaminants is understood at military ranges and ammunition production sites. Bioremediation of 2,4,6-trinitrotoluene (TNT), hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX), and related nitroaromatic compounds has met with mixed success, which is potentially due to the uncertainty of how energetic compounds are bound to different soil types. This study investigated the dissolution and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 17 publications
(37 reference statements)
3
32
0
Order By: Relevance
“…For example, Lynch et al [28] and Lynch [23] mined that explosive dissolution rates double with every 10 °C increase in temperature from 3 to 33 °C. In addition, solubility maxima may be influenced by soil physico-chemical properties which may influence explosive adsorption onto soil particles [29]). Furey et al [30] determined that geosorbents (e.g., iron, clay, humic acid) may influence the elution rate of TNT and RDX from soil.…”
Section: Dissolutionmentioning
confidence: 99%
“…For example, Lynch et al [28] and Lynch [23] mined that explosive dissolution rates double with every 10 °C increase in temperature from 3 to 33 °C. In addition, solubility maxima may be influenced by soil physico-chemical properties which may influence explosive adsorption onto soil particles [29]). Furey et al [30] determined that geosorbents (e.g., iron, clay, humic acid) may influence the elution rate of TNT and RDX from soil.…”
Section: Dissolutionmentioning
confidence: 99%
“…Research papers involving abiotic (N independent) processes most often reported the production of reduced products from TNT transformation (e.g. aminotoluenes) (Larson et al 2008). These products would bind to humic particles and aggregates (if present) or form dimers in solution.…”
Section: Discussionmentioning
confidence: 99%
“…Ainsworth et al [19] investigated the transformation of TNT and RDX in steam-sterilised soils, finding that TNT underwent abiotic transformation. Similarly, Larson et al [28] investigated the fate of TNT and RDX in 6 soils. The authors compared sterilised and unsterilised soils, and concluded that TNT and RDX transformation occurred in both the sterilised and unsterilised soils, though the transformation levels were higher in the unsterilised soils.…”
Section: Introductionmentioning
confidence: 99%